2009
DOI: 10.1007/978-3-642-10520-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Presentation of Large Hierarchies Using Treemaps

Abstract: Abstract. The presentation of large hierarchies is still an open research question. Especially, the time-consuming calculation of the visualization and the cluttered display lead to serious usability issues on the viewer side. Existing solutions mainly address appropriate visual representation and usually neglect considering system resources. We propose a holistic approach for the presentation of large hierarchies using treemaps and progressive refinement. The key feature of the approach is the mature use of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Based on this, animated tours-through-the-data can be provided or transmission can be tailored to the requirements of the user. 13 However, little is known about the application of progressive refinement in the visualization of abstract information. Our prior work started to fill this gap 13,14 and showed that wherever progressive refinement can be applied, it opens up a new way for efficient data handling and presentation.…”
Section: Device Adaptation and Progressive Refinement In Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, animated tours-through-the-data can be provided or transmission can be tailored to the requirements of the user. 13 However, little is known about the application of progressive refinement in the visualization of abstract information. Our prior work started to fill this gap 13,14 and showed that wherever progressive refinement can be applied, it opens up a new way for efficient data handling and presentation.…”
Section: Device Adaptation and Progressive Refinement In Visualizationmentioning
confidence: 99%
“…13 However, little is known about the application of progressive refinement in the visualization of abstract information. Our prior work started to fill this gap 13,14 and showed that wherever progressive refinement can be applied, it opens up a new way for efficient data handling and presentation. In the research we present here we apply the inherent principles of progressive refinement to the predictive adaptation of data displays for abstract data to the capabilities of the viewing device.…”
Section: Device Adaptation and Progressive Refinement In Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Future implementations of our method could significantly influence areas which use progressive refinement, such as Rosenbaum's [10] technique for device adaptation. As progressive refinement methods require generation of LODhierarchies for many types and sizes of multidimensional data, our method provides much of the necessary functionality.…”
Section: Conclusion and Possible Future Researchmentioning
confidence: 99%
“…1,14 Depending on the application domain, this can lead to faster data browsing, node search, or higher accuracy of task completion. These claims stem from their following inherent characteristics:…”
mentioning
confidence: 99%